Rekomendasi Penerima Remisi Menggunakan Metode AHP dan TOPSIS pada Lapas IIB Solok - Syalsabilla, Adinda; Yanto, Musli; Ariandi, Vicky (Universitas Putra Indonesia YPTK Padang, 2024)
Criminal law plays a crucial role in maintaining public order, and the correctional system is a crucial element in the administration of criminal law. Remission is a right for prisoners and becomes an essential aspect of corrections that provides incentives for good behavior during the rehabilitation period. Class IIB Solok Penitentiary faces challenges in the process of granting remission to prisoners without decision support systems. This study aims to develop a Decision Support System (DSS) using the Analytical Hierarchy Process (AHP) and the Technique for Order Preference by Similarity to Ideal Solution (TOPSIS) methods to provide recommendations for granting remission to prisoners. The research method involves using AHP to assign weights to relevant criteria in the remission process and TOPSIS to rank each alternative prisoner. This method is implemented by constructing a website using PHP programming language and MySQL database.The research dataset includes information about prisoners and criteria used in the remission decision-making process. The results show that the implementation of the DSS with AHP and TOPSIS methods can effectively provide recommendations for granting remission to prisoners. The system is capable of prioritizing prisoners based on their level of priority for receiving remission, enhancing efficiency in decision-making at Class IIB Solok Penitentiary. This study contributes to improving the objectivity and efficiency in the remission decision-making process, supporting effective criminal law administration